From Web Resources to Agricultural Ontology: a Method for Semi-Automatic Construction - Yuan-yuan WEI; Ru-jing WANG; Yi-min HU; Xue WANG (Journal of Integrative Agriculture)
In recent years, with the rapid development of information science, ontology becomes a popular research topic in the fields of knowledge engineering and information management. The reason for ontology being so popular is in large part due to what they promise: a shared and common understanding of some domain that can be communicated across people and computers. In the field of agriculture, FAO has started up the Agricultural Ontology Service (AOS) study project since 2001, AOS aims at providing knowledge service by agricultural domain ontology, it is the new seedtime for agricultural information service. However, establishing the ontology necessitates a great deal of expert assistance; manually setting it up would entail a lot of time, not to mention that there are only a handful of experts available. For this reason, using automatic technology to construct the ontology is a subject worth pursuing. A semi-automatic construction method for agricultural professional ontology from web resources is presented in this paper. For semi-structured web pages, the method automatically extracted and stored structured data through a program, built pattern mapping between relational database and ontology through human-computer interaction, and automatically generated a preliminary ontology, finally completed checking and refining by domain experts. The method provided a viable approach for ontology construction based on network resources in the actual work.